2006
DOI: 10.1097/01.mat.0000219066.21197.34
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Flow Rate Estimation of the NEDO PI Gyro Pump for Chronic BVAD Experiments

Abstract: In totally implantable ventricular assist device systems, measuring flow rate of the pump is necessary to ensure proper operation of the pump in response to the recipient's condition or pump malfunction. To avoid problems associated with the use of flow probes, several methods for estimating flow rate of a rotary blood pump used as a ventricular assist device have been studied. In the present study, we have performed a chronic animal experiment with two NEDO PI gyro pumps as the biventricular assist device for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This is crucial in designing an automatic, robust and responsive control system that effectively controls the blood flow according to the body's physiological needs and perturbations (Wakisaka et al 1997, Khalil et al 2008, Oshikawa et al 2000. Various groups have shown that such controllers are important to avoid and detect pumping states associated with abnormal flow conditions (Karantonis et al 2006, Ohuchi et al 2001, Amin et al 1997, Yuhki et al 1999, Endo et al 2001, Voigt et al 2005, Vollkron et al 2005, 2006, Fonseca et al 2008, Lee et al 2003.…”
Section: Estimation Of Pump Flow and Head In Rbpsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is crucial in designing an automatic, robust and responsive control system that effectively controls the blood flow according to the body's physiological needs and perturbations (Wakisaka et al 1997, Khalil et al 2008, Oshikawa et al 2000. Various groups have shown that such controllers are important to avoid and detect pumping states associated with abnormal flow conditions (Karantonis et al 2006, Ohuchi et al 2001, Amin et al 1997, Yuhki et al 1999, Endo et al 2001, Voigt et al 2005, Vollkron et al 2005, 2006, Fonseca et al 2008, Lee et al 2003.…”
Section: Estimation Of Pump Flow and Head In Rbpsmentioning
confidence: 99%
“…They obtained an estimation error of 0.27 L min −1 and a correlation coefficient of 0.875 for flow, as well as an estimation error of 6.77 mmHg and a correlation coefficient of 0.775 for pressure. Also, Ogawa et al (2006) have conducted a single chronic animal experiment to evaluate the flow estimation method proposed by Yoshizawa et al (2002) where a mean square error of 0.80 L min −1 and a correlation coefficient of 0.964 were obtained.…”
Section: Estimation Of Pump Flow and Head In Rbpsmentioning
confidence: 99%
See 3 more Smart Citations